2016
DOI: 10.1534/g3.116.033894
|View full text |Cite
|
Sign up to set email alerts
|

Preservation Analysis of Macrophage Gene Coexpression Between Human and Mouse Identifies PARK2 as a Genetically Controlled Master Regulator of Oxidative Phosphorylation in Humans

Abstract: Macrophages are key players involved in numerous pathophysiological pathways and an in-depth characterization of their gene regulatory networks can help in better understanding how their dysfunction may impact on human diseases. We here conducted a cross-species network analysis of macrophage gene expression data between human and mouse to identify conserved networks across both species, and assessed whether such networks could reveal new disease-associated regulatory mechanisms. From a sample of 684 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…We also found that regulatory pathway containing “phosphorylation” was the most enriched number pathway involved in both lncRNA and mRNA categories, highlighting its regulatory roles during TPMs activation. Previous reports showed that phosphorylation was associated with glycolysis during macrophage polarization [ 42 , 46 , 47 ]. This allows the speculation establish that glucose metabolic pathway and phosphorylation pathway might be connected and quite important in TPMs similar to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that regulatory pathway containing “phosphorylation” was the most enriched number pathway involved in both lncRNA and mRNA categories, highlighting its regulatory roles during TPMs activation. Previous reports showed that phosphorylation was associated with glycolysis during macrophage polarization [ 42 , 46 , 47 ]. This allows the speculation establish that glucose metabolic pathway and phosphorylation pathway might be connected and quite important in TPMs similar to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, in a recent plasma proteomic profiling study, 22 the F5 rs6027 and PLXDC2 rs927826 variants we found here associated TA B L E 3 Association of rs927826 genotypes with plasma FV antigen (FV:Ag) and activity (FV:C) in a sample of 60 patients from the MARTHA cohort NA: Expressions were not available Corresponding publication for each study: a [12]; b [13]; c [14]; d [15]; e [16]; f [17] F I G U R E 1 Impact of PLXDC2 gene silencing on F5 gene expression in liver. Abbreviation: KD = siRNA KnockDown.…”
Section: Discussionmentioning
confidence: 88%
“…We further examined the correlation between PLXDC2 and F5 gene expression in several genome-wide gene expression data from multiple cell lines and tissues. [12][13][14][15][16][17] In all investigated resources except macrophages, we observed positive correlations between PLXDC2 and F5 expressions, the strongest correlation (r = .45, P = 3.94 × 10 −14 ) being observed in liver ( Figure S5) where FV synthesis mainly occurs (Table 4). We also assessed the correlation of liver PLXDC2 expression with that of other coagulation genes expressed in the liver (F2, F7 and F10).…”
Section: Re Sultsmentioning
confidence: 96%
“…Genes involved in the regulation of inflammatory responses and gene–environment interactions were identified in macrophages from a set of mouse inbred strains, termed the hybrid mouse diversity panel (HMDP), while confounding factors such as environmental variation were minimized, making these datasets ideal for network biology and module identification. Macrophages were exposed to oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphatidylcholine (OxPAPC) or control treatment conditions [ 24 , 25 , 26 ]. Here, we analyzed the control and OxPAPC treatment data (329 samples), which were normalized using the robust multi-array average (RMA) method.…”
Section: Methodsmentioning
confidence: 99%